Co-VAN study: COVID-19 vaccine associated neurological diseases- an experience from an apex neurosciences centre and review of the literature. (February 2023) - Samim, M.M.; Dhar, Debjyoti; Arshad, Faheem; Anudeep, D.D.S.; Patel, Vishal G.; Neeharika, Sriram Ramalakshmi; Dhamija, Kamakshi; Ravindranath, Chowdary Mundlamuri; Yadav, Ravi; Raja, Pritam; Netravathi, M.; Menon, Deepak; et al.
Graphical abstract: Highlights: We retrospectively reviewed neurologic syndromes in temporal association with COVID-19 vaccination. The spectrum comprised CNS demyelination, Guillain Barre syndrome, stroke, encephalitis and myositis. Female sex had a greater pre-disposition. Majority of neurologic events occurred after the first dose (79.3%). Majority of the patients had favourable clinical outcome at discharge. The incidence of adverse events following COVID-19 vaccination is low and hence the benefits outweigh the risk. Abstract: Background: Recent studies have shown various neurological adverse events associated with COVID-19 vaccine. Objective: We aimed to retrospectively review and report the neurological diseases temporally associated with COVID-19 vaccine. Methods: We performed a retrospective chart review of admitted patients from 1st February 2021 to 30th June 2022. A total of 4672 medical records were reviewed of which 51 cases were identified to have neurological illness temporally associated with COVID-19 vaccination. Results: Out of 51 cases, 48 had probable association with COVID-19 vaccination while three had possible association. Neurological spectrum included CNS demyelination (n = 39, 76.5 %), Guillain-Barré-syndrome (n = 3, 5.9 %), stroke (n = 6, 11.8 %), encephalitis (n = 2, 3.9 %) and myositis (n = 1, 2.0 %). Female gender had a greater predisposition (F:M, 1.13:1). Neurological events were more commonly encountered after the first-dose (n = 37, 72.5%). The mean latency to onset of symptoms was 13.2 ± 10.7 days after the last dose of vaccination. COVIShield (ChAdOx1) was the most commonly administered vaccine (n = 43, 84.3 %). Majority of the cases with demyelination were seronegative (n = 23, 59.0 %) which was followed by anti-Myelin oligodendrocyte-glycoprotein associated demyelination (MOGAD) (n = 11, 28.2 %) and Neuromyelitis optica (NMOSD) (n = 5, 12.8 %). Out of 6 Stroke cases, 2 cases (33.3 %) had thrombocytopenia and coagulopathy. At discharge, 25/51 (49.0 %) of the cases had favourable outcome (mRS 0 to 1). Among six patients of stroke, only one of them had favourable outcome. Conclusion: In this series, we describe the wide variety of neurological syndromes temporally associated with COVID-19 vaccination. Further studies with larger sample size and longer duration of follow-up are needed to prove or disprove causality association of these syndromes with COVID-19 vaccination.